Studi Kasus Pembayaran Harta Anak dari Hasil Perkawinan Dalam Hukum Adat Maybrat - Palyama, Folce Elden; E, Esau (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This study aims to determine the procedures for payment of children's assets in Maybrat customary law and to determine the obstacles in the process of payment of children's assets in Maybrat customary law. This study was conducted in Wayer District, South Sorong Regency by taking 35 people as respondents and conducting in-depth observations regarding the issues studied. The findings found in this study include: Payment of children's assets is humanity and justice that differ in the abilities and progress and development of the Maybrat customary community who inhabit the Wayer district in South Sorong Regency. Maybrat customs are a reflection of the personality of a nation and are part of the customary process of the Indonesian nation that must be fulfilled by the man who takes a woman as his wife in Maybrat customs. Payment of children's assets usually occurs in the context of marriage or organizing certain traditional ceremonies according to Maybrat customs. This study is a contribution of thought to the development of legal science, especially Maybrat Customary Law in the implementation of payment of children's assets in Maybrat customary law. Marriage in Maybrat customs is a permanent relationship between two people who are recognized legally by the community concerned, namely Maybrat customs based on valid marriages. Marriage in the Maybrat indigenous community depends on Maybrat culture. Although they may be located outside the local village, the practices and goals may vary, but Maybrat customs are maintained. This research is descriptive with empirical legal research, providing a comprehensive, systematic overview of the situation under study.